Status Leukosit dan differential Leukosit Tikus Putih (Rattus norvegicus L.) Periode Laktasi Setelah Diberi Suplement Telur Puyuh Organik - Hasan Basri (Biota, 2018)
The purpose of this research is to know the status of the Leukocyte differential leukocyte and rats (Rattus norvegicus L.) lactation period after the grant of a supplement to the quail eggs are organic. This research is a type of experimental research with Random Design complete using 4 treatments and 5 replicates. The data obtained were analyzed with Anova, if there is a real difference continued test Duncan at 95% confidence level (α = 0.05). Analysis with the software SPSS 16.0 for windows. T0: Control Treatment; T1: (Rattus norvegicus L.) lactation period were given supplements of the eggs produced by quail fed commercial feed; T2: (Rattus norvegicus L.) lactation period were given supplements of the eggs produced by a given organic feed quail standard; T3: (Rattus norvegicus L.) lactation period were given supplements of the eggs produced by quail fed organic feed. Based on the number of leukocytes results showed different results real (P < 0.05), the number of neutrophils, basophils, esonofil shows a different result is not real (P > 0.05), whereas the number of lymphocytes showed different results real (P < 0.05). Supplementation of organic quail eggs could be maintain the condition Leukocyte status in the lactation period of (Rattus norvegicus L.).